Предмет:
Другие предметыАвтор:
аноним1) P(x) = x2 + 3x + 4; Q(x) = x – 2;
P(x) = x2 - 4x + 4 + 4x - 4 + 3x + 4 = (x-2)2 + 7x = (x-2)2 + 7(x - 2) + 14 =
= (x - 2) * (x - 2 + 7) + 14 = (x - 2) * (x + 5) + 14.
3) P(x) = 6x3 + 3x2 - 4x + 3; Q(x) = 2x + 1
P(x) = 6/8 * (8x3 + 3 * 4x2 + 3 * 2x + 1) - 6/8 * 12x2 - 6/8 * 6x - 6/8 + 3x2 - 4x + 3
= ¾ * (2x+1)3 - 9x2 - 9/2 * x - 3/4 + 3x2 - 4x + 3 =
= ¾ * (2x+1)3 - 6x2 - 17/2 * x + 9/4 =
= ¾ * (2x+1)3 - 3/2 * (4x2 + 4x + 1) + 6x + 3/2 - 17/2 * x + 9/4 =
= ¾ * (2x+1)3 - 3/2 * (2x+1)2 - 5/2 * x + 15/4 =
= ¾ * (2x+1)3 - 3/2 * (2x+1)2 - 5/4 * (2x + 1) + 5/4 + 15/4 =
= ¾ * (2x+1)3 - 3/2 * (2x+1)2 - 5/4 * (2x + 1) + 5 =
= ¼ * (2x + 1) * (2(2x + 1)2 - 6(2x + 1) - 5) + 5.
Можно упростить во второй скобке.
4) P(x) = 2x3 - 3x2 + 2x - 2; Q(x) = x2 + 2.
P(x) = 2(x3 + 2x) - x - 3x2 + 2x - 2 =
= 2x * (x2 + 2) - 3x2 - 2x - 2 = 2x * (x2 + 2) - 3(x2 + 2) - 2x - 2 + 6 =
= (x2 + 2) * (2x - 3) - 2x + 4.
Автор:
francaisblairДобавить свой ответ
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть